2002
DOI: 10.1007/s00018-002-8515-6
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis and CD10/neutral endopeptidase expression by jaspamide in HL-60 line cells

Abstract: Jaspamide (asplakinolide) is a natural peptide isolated from marine sponges of Jaspis species and has fungicidal and growth-inhibiting activities. We characterized the jasplakinolide-induced loss of viability by programmed cell death in the HL-60 human promyelocytic leukemia cell line and found that this process was accompanied by neutral endopeptidase (NEP)/CD10 expression on the surface of the apoptotic cells. HL-60 cells do not normally express detectable amounts of NEP/CD10 on their surface or intracytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 34 publications
1
22
0
3
Order By: Relevance
“…27 Still others have demonstrated that JP acts by inducing apoptosis through a caspase 3 dependent pathway. 31 Despite these hypothetical difficulties, our results support the claim that JP acts as a cytoskeleton stabilizer at the dose tested here (Figure 1), since all JP treated groups showed reversion of cytoskeletal disruption. This reversal was also observed in the groups in which disruption had previously been provoked by Swinholide, demonstrating Jasplakinolide's ability to counteract the effect of a disruptor of this kind.…”
Section: Discussionsupporting
confidence: 89%
“…27 Still others have demonstrated that JP acts by inducing apoptosis through a caspase 3 dependent pathway. 31 Despite these hypothetical difficulties, our results support the claim that JP acts as a cytoskeleton stabilizer at the dose tested here (Figure 1), since all JP treated groups showed reversion of cytoskeletal disruption. This reversal was also observed in the groups in which disruption had previously been provoked by Swinholide, demonstrating Jasplakinolide's ability to counteract the effect of a disruptor of this kind.…”
Section: Discussionsupporting
confidence: 89%
“…One of these peptides was tested on tumor lines. Research teams had found that this compound induces apoptosis in these tumor lines by activating caspase-3 and decreasing the expression of bcl-2 [26,28]. This same compound had anti mitotic effect by binding to tubulin (microtubules protein, a major component of the cytoskeleton) [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Further study reveals that cephalostatin 1 also inactivates the Bcl-2 via hyperphosphorylation by JNK [104]. Like cephalostatin 1, Jaspamide induces apoptosis by activation of caspase-3 and decrease of Bcl-2 protein levels, but it also involves increased Bax level via a caspase-independent pathway as an additional mechanism [105]. Another small compounds bromophenol derived from algae, bis(2,3-dibromo-4,5-dihydroxybenzyl) ether, induces mitochondrial apoptosis in K562 cells via activation of caspases and changes the Bcl-2/Bax in vitro [106].…”
Section: Compounds That Have Multiple Targets On Apoptotic Pathwaysmentioning
confidence: 97%